Kingdom of the Netherlands : Aruba. (IMF Staff Country Reports; Country Report, 2020)
This Technical Assistance report on Kingdom of the Netherlands-Aruba focuses on the mission undertaken to assist the Central Bureau of Statistics (CBS) in assessing and improving the national accounts. The CBS plans to recompile and disseminate the revised annual current price estimates by January 2020, and improved constant 2013 price estimates by June 2020. The mission and the Director of the CBS met with the Minister of Finance, Economic Affairs and Culture to discuss the rebased estimates and the 2020-2025 action plan. The budget, staffing, and data coordination plans of the CBS were also discussed. The Minister agreed to establishing formal data coordination agreements between the CBS and other government institutions, and on the need for the legislation and related reporting procedures to be strengthened. She also agreed to the 2020-2025 action plan to implement the Special Data Dissemination Standard for real-sector statistics, the need for benchmark and regular surveys, and to incrementally increasing the CBS budget and staffing, subject to Cabinet approval.